ANALISIS YURIDIS TERHADAP TINDAKAN ANARKIS DALAM AKSI DEMONSTRASI YANG BERUJUNG PADA PENJARAHAN RUMAH ANGGOTA DPR - Unwanul Hubby (JOURNAL OF LAW AND NATION, 2025)
Demonstrations are a constitutional right guaranteed by Article 28E (3) of the 1945 Constitution and Law No. 9 of 1998. However, in practice, this freedom often escalates into anarchic acts that harm others. This study is motivated by the August 2025 demonstrations that culminated in the looting of several members of the Indonesian House of Representatives’ residences. The research focuses on analyzing the limits of freedom of expression during demonstrations, the validity of repressive state actions, and the effectiveness and proportionality of law enforcement against looting crimes under the Indonesian Criminal Code (KUHP) and human rights principles. The method used is normative legal research with statutory, conceptual, and case approaches, relying on primary, secondary, and tertiary legal materials. The findings indicate that freedom of expression is not absolute; looting constitutes a criminal offense under the KUHP (Articles 362, 363, 365, 406, 170) and violates property rights protected by the 1945 Constitution and the Human Rights Law. Law enforcement officers are authorized to act repressively as long as actions remain proportional, legal, and accountable. Nevertheless, weak early detection, inadequate initial responses, and potential excessive use of force undermine the effectiveness and proportionality of law enforcement, leading to erosion of state legitimacy and degradation of public democratic space.